Implementasi Konsep Mottainai sebagai Upaya Pelestarian Lingkungan dalam Anime Mottainai Baasan karya Mariko Shinjuu - Deanahara, Cindy Rut; Budiana, I Made; Ari Sulatri, Ni Luh Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023)DO - 10.24843/JS.2023.v05.i01.p05, 2023)
This article discusses about the environmental problem and the implementation of mottainai to preserve the environment in Mottainai Baasan anime. The method used in this article was content analysis with a qualitative approach. The ecocriticism literary theory by Garrard and an environmental ethics theory by Keraf are used as the basic theorethical. The results indicate that in the anime, four environmental problems are found which include soil pollution, water pollution, food waste, and energy waste, which occur due to a lack of understanding about environmental conservation. Environmental problems that continue to occur make Japanese people strive to preserve the environment by implementing the mottainai concept. The implementation of mottainai is reflected in the environmental ethics principle, such as: 1) respect for nature, including the awareness that environment has a value and allowing living creature in the environment to live and grow; 2) moral responsibility for nature, including awareness to protect the environment and prevent environmental damage; 3) caring for nature, including caring for living beings who experience difficulties and awareness that the environment has the right to be protected; 4 simple lifestyle and in harmony with the environment; including maximizing the function of an object to reduce consumptive behavior.